PREDICTIVE VALUE OF ACCESS TO RESEARCH GRANTS ON ACADEMIC STAFF RESEARCH PRODUCTIVITY IN UNIVERSITIES IN ANAMBRA STATE. (International Nexus Multidisciplinary Research Journal, 2026)
This study examined the predictive value of access to research grants on academic staff research productivity in universities in Anambra State, Nigeria. A correlational research design was adopted for the study. The population comprised 3,276 academic staff from two public universities, out of which a sample of 356 respondents was selected using a multi-stage sampling procedure. Data were collected using researcher-developed questionnaires that were validated and tested for reliability. The data were analysed using simple linear regression and regression t-test at a 0.05 level of significance.The findings revealed that access to research grants has a strong positive predictive value on academic staff research productivity, with a correlation coefficient (R) of 0.735 and an R² value of 0.540, indicating that 54% of the variation in research productivity is explained by access to research grants. The hypothesis test showed that the predictive value is statistically significant (p < 0.05). The study concluded that access to research grants significantly enhances research productivity among academic staff. It was recommended that government and relevant agencies should increase funding opportunities and create diverse funding sources to support research activities in universities.